Comparison of the Effectiveness of a Parenting Package Based on Maternal Parenting Needs Response with Organization Skills Training on Overparenting and Parenting Competence in Parents of Children Aged 8-12 with Sluggish Cognitive Tempo Disorder - Arjhang, Nasim; Bahramipourisfahani, Mansoureh; Yousefi, Zahra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of a parenting package based on responding to the parenting needs of mothers with organization skills training on overparenting and parenting competence in parents of children aged 8-12 with sluggish cognitive tempo disorder. Methodology: The statistical population of this quasi-experimental study included all mothers with children aged 8-12 with sluggish cognitive tempo disorder in the 2022-2023 academic year in the city of Isfahan. The sample size consisted of 45 mothers of children with sluggish cognitive tempo disorder, selected based on the Sluggish Cognitive Tempo Questionnaire (Parent Form) and purposeful sampling criteria, and randomly assigned to two experimental groups and one control group (each group consisting of 15 participants). The experimental groups received separate training sessions of the parenting package based on maternal needs and organization skills training, each conducted over 12 sessions of 60 minutes. Data were collected using the Sluggish Cognitive Tempo Questionnaire (Parent Form), the Overparenting Questionnaire, and the Parenting Competence Questionnaire, and were analyzed using descriptive statistics including mean and standard deviation, and inferential statistics using repeated measures analysis of variance. Findings: The results showed that the parenting package based on the needs of mothers of children with sluggish cognitive tempo disorder was more effective than organization skills training in enhancing overparenting and parenting competence. Additionally, both experimental groups showed a significant impact compared to the control group (p